Haemophilia A and haemophilia B - Klamroth, R.; Orlovic, M.; Kubicek-Hofman, C.; Gottstein, S. (Hämostaseologie, 2010)
Haemophilia B (HB) was described in 1952 as a single disease for the first time. In comparison to haemophilia A (HA) the bleeding tendency seemed to be less severe. The aim of this study was to investigate this hypothesis in all patients with HA and HB treated in the haemophilia care center of the Vivantes Klinikum. Patients, methods: All patients with severe HA and HB treated at the haemophilia care center were included. We evaluated the regimen of replacement therapy and factor concentrate consumption within the last 5 years (1/2004 to 12/2008). Intracerebral bleeds were analysed over the whole life span of the included patients. Results: 111/181 patients with HA had the severe form and 12/34 patients severe HB. 4/12 patients with severe HB had a history of intracerebral bleeding in comparison to 5/111 patients with severe HA. 2/8 adult patients with severe HB used a prophylactic treatment with factor concentrates (mean consumption 1289 IU factor IX/kg BW/ year) in contrast to 60/95 adult patients with HA (mean consumption 2109 IU factor VIII /kg BW/year). Conclusion: The data suggest a milder bleeding type of patients with severe HB in comparison to patients with severe HA but may be patients with severe HB are at higher risk for intracerebral bleeds.
Keywords: Haemophilia B